Administration of metformin in type 2 diabetes mellitus patients with chronic kidney disease; facts and myths - Mohsen Akhavan Sepahi; Bhaskar VKS Lakkakula; Steven James Kellner; Rohollah Valizadeh (Society of Diabetic Nephropathy Prevention, 2020)
There are few publications reporting adverse effects of metformin for patients with type 2 diabetes mellitus (T2DM) and chronic kidney disease (CKD). Although some of these reports have made big claims about the adverse effects of metformin in patients with renal failure, the majority of studies showed a superior safety profile for metformin compared with other antidiabetic medications in these patients. Further, metformin use is not contributing to an increased incidence of acute kidney injury (AKI). In conclusion, we suggest that a low dose of metformin is safe to use in patients with or without CKD. Multicenter randomized trials are required to further discover the benefits of the risk of metformin therapy in different stages of CKD and its effect on progression of CKD.